Beyond Flexibility: Management Innovation and Algorithmic Control in the Gig Economy Era - Purba, Mercidominick Fidelius Conrad Menachem; Sari, Evi Thelia; Purba, Lasman Parulian (Airlangga Journal of Innovation Management, 2026)
The gig economy is growing rapidly and is creating new challenges for those responsible for managing workers. The expansion of digital platforms and technological systems has significantly influenced how work is organized and managed in modern labor markets. This study aims to examine how the gig economy affects the management of workers and to understand how technological systems influence human resource management practices. This study aims to examine how the gig economy affects the management of workers and to understand how technological systems influence human resource practices. The results show that digital systems and algorithms are increasingly used to determine task allocation and worker management. These technological developments are significantly transforming the role of managers in the gig economy. The study also finds that gig economy experiences higher vulnerability due to limited legal protection compared to formal workers. The study reveals a paradox between the flexibility desired by workers and the job instability that accompanies gig work. This condition requires adaptive human resource management strategies. Strategic and regulatory updates are also needed to address the emerging challenges in the gig economy. The findings suggest that the HRM function needs to transform in order to manage boundary-less careers in the digital era. Furthermore, future research is recommended to explore the role of artificial intelligence in human resource management practices.